2014
DOI: 10.1021/es4050314
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Composition of Emerging Quaternary Ammonium Compounds in Municipal Sewage Sludge in China

Abstract: Quaternary ammonium compounds (QACs) have raised considerable attention due to their wide commercial applications and recent discovery of unknown persistent analogues in aqueous environment. In this work, the occurrence and distribution of alkyltrimethylammonium (ATMAC), benzylakyldimethylethylammonium (BAC) and dialkyldimethylammonium (DADMAC) homologues were investigated in fifty-two municipal sewage sludge samples. ATMAC C10−18, BAC C8−18 and paired DADMAC C8:8-C18:18 as well as emerging homologues such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 40 publications
4
113
0
Order By: Relevance
“…The qacEΔ1 genes represent a mechanism for antibiotic efflux resistance genes, which are commonly embedded in integron resistance cassettes (Singh et al 2005;Koczura et al 2016). The high level of qacEΔ1 genes may result from the overuse and abuse of quaternary ammonium compounds which have widespread commercial applications (Ruan et al 2014;Wassenaar et al 2015) that may lead to an increasing prevalence of resistance genes impacting human health. We also found high levels of vancomycin resistance genes which are relatively rare in natural environments with an absolute abundance range from 4.44 × 10 6 to 8.17 × 10 8 copies per L. Vancomycin is a fallback therapy against microorganisms in hospitals suggesting that wastewater from medical facilities could be a source of ARGs as inferred in previous studies (Zhu et al 2017;D'Costa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The qacEΔ1 genes represent a mechanism for antibiotic efflux resistance genes, which are commonly embedded in integron resistance cassettes (Singh et al 2005;Koczura et al 2016). The high level of qacEΔ1 genes may result from the overuse and abuse of quaternary ammonium compounds which have widespread commercial applications (Ruan et al 2014;Wassenaar et al 2015) that may lead to an increasing prevalence of resistance genes impacting human health. We also found high levels of vancomycin resistance genes which are relatively rare in natural environments with an absolute abundance range from 4.44 × 10 6 to 8.17 × 10 8 copies per L. Vancomycin is a fallback therapy against microorganisms in hospitals suggesting that wastewater from medical facilities could be a source of ARGs as inferred in previous studies (Zhu et al 2017;D'Costa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Boyaci et al (2014) used a zwitterionic detergent as matrix modifier in water samples. Others employed octadecylbenzenesulfonate (Ruan et al 2014) or the detergent Marlon A375, a sodium alkylbenzenesulfonate (Martínez-Carballo et al 2007a), for sewage sludge extraction as hydrophobic ion pair complexing agent. Chen (2014) found that trifluroacetic acid (TFA) added at 0.1% (volume) in methanol/water high pressure liquid chromatography (HPLC)-reduced peak tailing compared to the most widely used formiate, indicating better ion-pairing properties.…”
Section: Analytical Methods Used For Qaac Analysis In Environmental Mmentioning
confidence: 99%
“…For extractions procedures that need to be developed for soil sample screening, there are several recent multi-compound protocols for sewage-sludge available, which can serve as a point of reference (Martínez-Carballo et al 2007a;Li and Brownawell 2009;Li et al 2014a;Ruan et al 2014). Ruan et al (Ruan et al 2014) reported lowest limits of quantitation between 1 and 4 ng g -1 and presented the most versatile method. They were able to quantify 23 QAAC homologues from Chinese sewage sludge.…”
Section: Analytical Methods Used For Qaac Analysis In Environmental Mmentioning
confidence: 99%
See 2 more Smart Citations